Reform of Teaching Methods in Auditing: Design of Blended Online and Offline Teaching - Chen, Jin (International Journal of Social Sciences and Public Administration, 2023)
In the era of "Internet plus", information technology has changed the accounting environment, and the accounting profession has undergone subversive changes. In this context, the key issues that need to be addressed in curriculum and teaching reform are how to match the course content with the knowledge, abilities, and literacy of current graduates, how to use internet platforms to innovate teaching methods, reform assessment and evaluation systems, and change students’ learning habits. Implement student-centered approach. The content of auditing is relatively obscure and difficult to understand. This article aims to reform teaching methods and use a blended online and offline teaching approach, in order to make students truly the main body of the classroom, improve their participation in teaching, and cultivate their ability to think independently.